Graphene oxide reinforced recycled aggregate ultra-high performance concrete and preparation method thereof
By using graphene oxide in ultra-high performance concrete to enhance regenerated aggregates, combined with limestone calcined tanned soil system and batch spraying and mixing technology, the impact of regenerated aggregates on concrete performance is solved, and efficient and economical performance improvement is achieved.
Patent Information
- Application Number
- CN202310024376.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-01-09
AI Technical Summary
When using recycled aggregates, existing ultra-high performance concrete faces the problems of performance influence such as strength and durability, and the agglomeration effect of graphene oxide leads to limited enhancement effect.
Graphene oxide is used to enhance the regenerated aggregate, slag and regenerated powder are added as auxiliary gelling materials through limestone calcined clay system, and intermittent spraying and stirring are used to make the graphene oxide evenly distributed on the surface of the aggregate, achieving a relatively low dosage enhancement effect.
It has achieved the reduction of costs while significantly improving the strength and durability of ultra-high performance concrete, solved the impact of recycled aggregates on concrete performance, and explored a sustainable UHPC preparation method.
Smart Images

Figure CN116217162B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and specifically relates to a graphene oxide reinforced recycled aggregate ultra-high performance concrete and a preparation method thereof. Background Art
[0002] Ultra-high performance concrete (UHPC) is a cement-based material with high strength, high toughness and high durability. Due to the vigorous development of the domestic construction industry, traditional concrete can no longer meet the needs of some projects, and the rise of UHPC has followed. However, because it requires high-quality materials, the cost has increased sharply, and a large amount of environmental pollution is also its main problem. With the deepening of China's urbanization process, there is a serious shortage of construction raw materials, especially natural river sand, so there is an urgent need to find materials that can replace natural river sand; on the other hand, my country has shifted from high-speed development to high-quality development, and there are a lot of industrial waste disposal problems; due to the demolition of old communities, the amount of construction waste in the city is increasing, and the period of landfilling construction waste is too long, so there is an urgent need to find a green and effective method.
[0003] In the face of the above problems, the use of recycled aggregates to prepare ultra-high performance concrete should be an economical, green and efficient solution. This will not only solve the problem of handling some construction waste, but also greatly reduce the material cost of UHPC. However, the impact of the addition of recycled aggregates on the strength, durability and other properties of concrete is a current difficulty. For example, the presence of a large amount of old mortar on the surface of recycled aggregates will seriously affect the mechanical properties of UHPC. Some studies have tried to use graphene oxide (GO) to modify recycled aggregates, but when GO is added, agglomeration effects are observed, which seriously affect the enhancement effect. If the dosage is increased to enhance the effect, not only will the cost increase, but the fluidity of UHPC will also drop significantly, seriously affecting its working performance. Therefore, how to apply recycled aggregates to ultra-high performance concrete and enhance the performance of concrete while reducing costs is a technical problem that needs to be solved in this field. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a graphene oxide reinforced recycled aggregate ultra-high performance concrete and a preparation method thereof in view of the deficiencies in the prior art. Regenerated sand is used to replace natural river sand, slag and recycled micropowder are added to the limestone calcined clay system as auxiliary cementitious materials, and graphene oxide is used to reinforce the recycled aggregate. Intermittent spraying and stirring are used to evenly distribute the graphene oxide on the surface of the aggregate, and a significant reinforcement effect is achieved with a relatively low dosage, thereby obtaining ultra-high performance concrete with excellent performance.
[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a graphene oxide reinforced recycled aggregate ultra-high performance concrete, which comprises the following raw materials in parts by weight: 570-650 parts of cement, 150-180 parts of slag, 100-150 parts of metakaolin, 80-120 parts of limestone powder, 300-440 parts of regenerated sand, 50-80 parts of regenerated micro powder, 700-1000 parts of quartz sand, 100-200 parts of quartz powder, 30-60 parts of polycarboxylate water reducer, 180-280 parts of water, and 0.5-0.8 parts of graphene oxide; and also comprises steel fiber, the volume of the steel fiber being 1.5-2.2% of the total volume of the concrete.
[0006] In the above scheme, the cement is ordinary Portland cement.
[0007] In the above scheme, the particle size of the slag is less than 40 μm, and the sum of the contents of CaO, MgO, SiO2 and MnO is greater than 90%.
[0008] In the above scheme, the SiO2 content of the metakaolin is 40-60%, the Al2O3 content is 30-50%, and the loss on ignition is ≤5%.
[0009] In the above scheme, the particle size of the limestone powder is less than 1 mm, the CaO content is 40-60%, the SiO2 content is 20-40%, the Al2O3 content is ≤10%, and the ignition loss is ≤5%.
[0010] In the above scheme, the regenerated sand is medium sand in zone II made by crushing, washing and screening waste concrete, and its fineness modulus is 2.3 to 2.8.
[0011] In the above scheme, the regenerated micro powder is a fine powder produced during the crushing process of construction waste, and its particle size is less than 0.16 mm.
[0012] In the above scheme, the particle size of the quartz sand is 10-70 meshes, its SiO2 content is 90-99%, and its Fe2O3 content is 0.06-0.02%.
[0013] In the above scheme, the particle size of the quartz powder is 300-400 meshes, and its SiO2 content is 90-99%.
[0014] In the above scheme, the polycarboxylate water reducer is a high-efficiency naphthalene-based polycarboxylate water reducer with a water reduction rate of >30%.
[0015] In the above scheme, the sheet diameter of the graphene oxide is 0.5 to 3 μm and the thickness is 1.1 to 1.2 nm.
[0016] In the above solution, the diameter of the steel fiber is 12-16 mm and the length is 0.18-0.22 mm.
[0017] The present invention also provides a method for preparing graphene oxide reinforced recycled aggregate ultra-high performance concrete, comprising the following steps:
[0018] 1) Cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz powder are mixed and stirred at high speed to obtain a solid mixture A;
[0019] 2) pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, stirring at a high speed, to obtain a solid mixture B;
[0020] 3) Mixing polycarboxylate water reducer, graphene oxide and water, wherein the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, and stirring evenly to prepare a dispersion C;
[0021] 4) placing the solid mixture B in a high-speed stirring state, and spraying the dispersion liquid C intermittently therein until the two are completely mixed, thereby obtaining a solid-liquid mixture D;
[0022] 5) adding steel fiber to the solid-liquid mixture D and stirring at high speed to obtain a mixture E;
[0023] 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and cured to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0024] In the above scheme, the speed of the high-speed stirring is 2000-3000 rpm.
[0025] In the above scheme, the stirring time in step 1), step 2) and step 5) is 5 to 8 minutes.
[0026] In the above scheme, the intermittent spraying process is to spray solution C onto the surface of solid mixture B for 30 to 60 seconds every 1 to 2 minutes, and control the spraying flow rate so that the total duration of step 4) is controlled within 10 to 15 minutes.
[0027] In the above scheme, the curing temperature is 20±2°C, the humidity is greater than 95%, and the curing time is 7 to 28 days.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1) The present invention crushes, cleans and sieves waste concrete to make regenerated sand, uses fine powder produced by crushing construction waste as regenerated micropowder, and uses the regenerated sand to replace natural river sand and part of quartz sand, and the regenerated micropowder to replace part of quartz micropowder, which are applied to the preparation of ultra-high performance concrete. This not only solves the problem of handling part of construction waste, but also plays a certain role in alleviating the shortage of materials in the construction industry. At the same time, it also greatly reduces the material cost of ultra-high performance concrete, and explores a sustainable UHPC preparation method, which has important economic value and environmental significance.
[0030] 2) The present invention uses a limestone calcined clay system with slag and recycled micropowder as auxiliary cementitious materials, which can replace part of the cement. The additional alkaline environment and calcium hydroxide provided by the system can improve the degree of hydration, promote the volcanic ash reaction characteristics and the later strength growth rate; and the microcrystalline nucleus effect of the silicon and calcium particles in the limestone powder promotes cement hydration, which can reduce the calcium hydroxide content in the hydration product and reduce the porosity, thereby improving the mechanical properties and durability of UHPC.
[0031] 3) The present invention uses graphene oxide to enhance recycled aggregate, providing a filler effect to enhance the compactness of the cement matrix, and graphene oxide can provide additional hydration product nucleation sites during the cement hydration process, promote cement hydration and regulate the formation of cement hydration crystals, making the cement matrix more dense and uniform; Different from the traditional direct mixing method, the present invention adopts a spraying method to add graphene oxide, which can achieve a good dispersion effect, solve its agglomeration problem, and make the graphene oxide evenly distributed on the aggregate surface, so as to achieve a significant enhancement effect with a lower dosage, and obtain ultra-high performance concrete with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 The present invention is a flow chart for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0033] Figure 2 This is a schematic diagram of the structure of a stirring device with a spray system used in an embodiment of the present invention.
[0034] In the figure: 1-operation panel; 2-power supply; 3-motor; 4-solution inlet; 5-spraying system; 6-stirring blade. DETAILED DESCRIPTION
[0035] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0036] In the following examples, cement is ordinary Portland cement; the average particle size of slag is 38 μm, and the sum of its CaO, MgO, SiO2 and MnO contents is 92%; the SiO2 content of metakaolin is 45%, the Al2O3 content is 38%, and the loss on ignition is 3%; the average particle size of limestone powder is 0.15 mm, and its CaO content is 52%, SiO2 content is 36%, Al2O3 content is 8%, and the loss on ignition is 3%; the regenerated sand is the medium sand of zone II made by crushing, washing and screening the waste concrete, and the fineness modulus is 2. 7. The recycled micro powder is a fine powder produced in the crushing process of construction waste, and its particle size is 0.044 mm. The particle size of quartz sand is 40 mesh, and its SiO2 content is 96%, and its Fe2O3 content is 0.03%. The particle size of quartz powder is 325 mesh, and its SiO2 content is 95%. The polycarboxylate water reducer is a high-efficiency naphthalene polycarboxylate water reducer with a water reduction rate of 35%. The flake size distribution range of graphene oxide is 0.5-3 μm, and the average thickness is 1.1-1.2 nm. The diameter of the steel fiber is 13 mm and the length is 0.18 mm.
[0037] Example 1
[0038] A graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following raw materials in parts by weight: 570 parts of cement, 150 parts of slag, 100 parts of metakaolin, 80 parts of limestone powder, 330 parts of regenerated sand, 60 parts of regenerated micro powder, 770 parts of quartz sand, 140 parts of quartz stone powder, 45 parts of polycarboxylate water reducer, 198 parts of water, and 0.6 parts of graphene oxide; and also comprises steel fiber, wherein the volume of the steel fiber is 2% of the total volume of the concrete.
[0039] The method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following steps:
[0040] 1) adding cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz stone powder into a stirring device, mixing, and stirring at a high speed of 2000 rpm for 5 minutes to obtain a solid mixture A;
[0041] 2) pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, and stirring at a high speed of 2000 rpm for 5 minutes to obtain a solid mixture B;
[0042] 3) Mixing polycarboxylate water reducer, graphene oxide and water, wherein the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, and stirring evenly to prepare a dispersion C;
[0043] 4) placing the solid mixture B in a high-speed stirring state at a rotation speed of 2000 rpm, spraying the solution C onto the surface of the solid mixture B for 30 seconds every 1 minute until the two are completely mixed, and controlling the spraying flow rate so that the total duration is controlled within 10 minutes to obtain a solid-liquid mixture D;
[0044] 5) adding steel fiber to the solid-liquid mixture D, and stirring at a high speed of 2000 rpm for 5 min to obtain a mixture E;
[0045] 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and the mixture is cured for 28 days at a temperature of 20±2° C. and a humidity of more than 95% to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0046] Example 2
[0047] A graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following raw materials in parts by weight: 650 parts of cement, 180 parts of slag, 150 parts of metakaolin, 120 parts of limestone powder, 403 parts of recycled sand, 73 parts of recycled micropowder, 939 parts of quartz sand, 169 parts of quartz stone powder, 53 parts of polycarboxylate water reducer, 242 parts of water, and 0.7 parts of graphene oxide; and also comprises steel fiber, wherein the volume of the steel fiber is 1.8% of the total volume of the concrete.
[0048] The method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following steps:
[0049] 1) adding cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz stone powder into a stirring device, mixing, and stirring at a high speed of 2500 rpm for 6.5 min to obtain a solid mixture A;
[0050] 2) pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, and stirring at a high speed of 2500 rpm for 6.5 minutes to obtain a solid mixture B;
[0051] 3) Mixing polycarboxylate water reducer, graphene oxide and water, wherein the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, and stirring evenly to prepare a dispersion C;
[0052] 4) placing the solid mixture B in a high-speed stirring state at a rotation speed of 2500 rpm, spraying the solution C on the surface of the solid mixture B for 40 seconds every 1.5 minutes until the two are completely mixed, and controlling the spraying flow rate so that the total duration is controlled within 12 minutes to obtain a solid-liquid mixture D;
[0053] 5) adding steel fiber to the solid-liquid mixture D, and stirring at a high speed of 2500 rpm for 6.5 min to obtain a mixture E;
[0054] 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and the mixture is cured for 28 days at a temperature of 20±2° C. and a humidity of more than 95% to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0055] Example 3
[0056] A graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following raw materials in parts by weight: 600 parts of cement, 160 parts of slag, 120 parts of metakaolin, 90 parts of limestone powder, 355 parts of regenerated sand, 64 parts of recycled micropowder, 828 parts of quartz sand, 149 parts of quartz powder, 47 parts of polycarboxylate water reducer, 213 parts of water, and 0.8 parts of graphene oxide; and also comprises steel fiber, wherein the volume of the steel fiber is 1.6% of the total volume of the concrete.
[0057] The method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following steps:
[0058] 1) adding cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz stone powder into a stirring device, mixing, and stirring at a high speed of 3000 rpm for 8 minutes to obtain a solid mixture A;
[0059] 2) pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, and stirring at a high speed of 3000 rpm for 8 minutes to obtain a solid mixture B;
[0060] 3) Mixing polycarboxylate water reducer, graphene oxide and water, wherein the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, and stirring evenly to prepare a dispersion C;
[0061] 4) placing the solid mixture B in a high-speed stirring state at a rotation speed of 3000 rpm, spraying the solution C onto the surface of the solid mixture B for 50 s every 2 min until the two are completely mixed, and controlling the spraying flow rate so that the total duration is controlled within 15 min, to obtain a solid-liquid mixture D;
[0062] 5) adding steel fiber to the solid-liquid mixture D, and stirring at a high speed of 3000 rpm for 8 min to obtain a mixture E;
[0063] 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and the mixture is cured for 28 days at a temperature of 20±2° C. and a humidity of more than 95% to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0064] Comparative Example 1
[0065] The only difference between Comparative Example 1 and Example 2 is that no graphene oxide is added.
[0066] Comparative Example 2
[0067] The difference between Comparative Example 2 and Example 2 is that: during the preparation process, after the polycarboxylate water-reducing agent, graphene oxide and water are made into a dispersion C, they are not added by spraying, but directly mixed; that is, step 4) is replaced by: the dispersion C is directly added to the solid mixture B, and the mixture is stirred at high speed to obtain a solid-liquid mixture D.
[0068] Comparative Example 3
[0069] A graphene oxide reinforced recycled aggregate ultra-high performance concrete, comprising the following raw materials in parts by weight:
[0070] 630 parts of cement, 300 parts of fly ash, 110 parts of silica fume, 328 parts of regenerated sand, 766 parts of quartz sand, 42 parts of polycarboxylic acid water reducer, 187 parts of water, and 0.7 parts of graphene oxide; calculated by volume percentage, the regenerated sand ultra-high performance concrete is also mixed with 1.6% of steel fiber.
[0071] The method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following steps:
[0072] 1) adding cement, fly ash, silica fume and quartz sand into a stirring device and mixing them, and stirring them at a high speed of 2500 rpm for 6.5 min to obtain a solid mixture A;
[0073] 2) pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, and stirring at a high speed of 2500 rpm for 6.5 minutes to obtain a solid mixture B;
[0074] 3) Mixing polycarboxylate water reducer, graphene oxide and water, wherein the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, and stirring evenly to prepare a dispersion C;
[0075] 4) placing the solid mixture B in a high-speed stirring state at a rotation speed of 2500 rpm, spraying the solution C on the surface of the solid mixture B for 40 seconds every 1.5 minutes until the two are completely mixed, and controlling the spraying flow rate so that the total duration is controlled within 12 minutes to obtain a solid-liquid mixture D;
[0076] 5) adding steel fiber to the solid-liquid mixture D, and stirring at a high speed of 2500 rpm for 6.5 min to obtain a mixture E;
[0077] 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and the mixture is cured for 28 days at a temperature of 20±2° C. and a humidity of more than 95% to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
[0078] Performance tests were performed on Examples 1-3 and Comparative Examples 1-3, wherein the compressive strength test method was based on GB50010 "Concrete Structure Design Code" to test the 28-day strength, and the four-point flexural strength test was based on GB / T17671 "Cement Mortar Strength Test Method", using a standard prism specimen size of 160×40×40mm to test the 28-day strength. The results are shown in Table 1.
[0079] Table 1
[0080] serial number Slump(mm) Compressive strength(MPa) Four-point flexural strength (MPa) Example 1 173 167 27.3 Example 2 177 178 29.4 Example 3 175 180 29.9 Comparative Example 1 180 140 22.3 Comparative Example 2 148 151 25.8 Comparative Example 3 172 158 26.0
[0081] The test results show that the compressive strength of the graphene oxide enhanced recycled aggregate ultra-high performance concrete in the three embodiments exceeds 160MPa, and can reach up to 180MPa. The four-point flexural strength exceeds 27MPa, and can reach up to 29.9MPa. With the increase of spraying time and the increase of graphene oxide content, the increase of compressive strength and four-point flexural strength in Example 3 is significantly reduced, and the slump decreases slightly, indicating that the increase of graphene oxide content does not increase its strength linearly. We must select the appropriate dosage according to the actual situation to achieve green and economic while meeting the strength requirements.
[0082] In Comparative Example 1, graphene oxide was not added. Due to the low strength of the regenerated sand itself, it was not modified with graphene oxide, and the compressive and four-point flexural strengths of Comparative Example 1 were both low. The preparation method of graphene oxide-enhanced recycled aggregate ultra-high performance concrete in Comparative Example 2 lacks the spraying operation step and adopts a direct mixing method. Therefore, the slump, compressive and four-point flexural strengths of Comparative Example 2 are all lower than those of the three embodiments. The reason is that the addition method causes the graphene oxide to be unable to be evenly dispersed, thereby affecting the enhancement effect. Comparative Example 3 uses a conventional fly ash silica fume system to prepare regenerated sand ultra-high performance concrete. It can be seen that the strength of the ultra-high performance concrete prepared using a limestone calcined clay system is significantly enhanced. This is because the limestone calcined clay system can refine the matrix pore size to improve strength and durability.
[0083] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.
Claims
1. A graphene oxide reinforced recycled aggregate ultra-high performance concrete, characterized in that: The concrete comprises the following raw materials in parts by weight: 570-650 parts of cement, 150-180 parts of slag, 100-150 parts of metakaolin, 80-120 parts of limestone powder, 300-440 parts of regenerated sand, 50-80 parts of regenerated micro powder, 700-1000 parts of quartz sand, 100-200 parts of quartz powder, 30-60 parts of polycarboxylate water reducer, 180-280 parts of water, and 0.5-0.8 parts of graphene oxide; and also comprises steel fiber, the volume of which is 1.5-2.2% of the total volume of the concrete; The method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete comprises the following steps: 1) Mix cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz powder, and stir at high speed to obtain a solid mixture A; 2) Pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; adding the regenerated sand in a saturated surface dry state to the solid mixture A, stirring at a high speed, to obtain a solid mixture B; 3) Mix polycarboxylate water reducer, graphene oxide and water, the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, stir evenly to prepare dispersion C; 4) The solid mixture B is placed in a high-speed stirring state, and the dispersion C is sprayed therein for 30 to 60 seconds every 1 to 2 minutes until the two are completely mixed. The total time is controlled within 10 to 15 minutes to obtain a solid-liquid mixture D; 5) Add steel fiber to the solid-liquid mixture D and stir at high speed to obtain a mixture E; 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and cured to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
2. The graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The regenerated sand is medium sand in zone II made by crushing, washing and screening waste concrete, and has a fineness modulus of 2.3-2.8; the regenerated fine powder is fine powder produced in the crushing process of construction waste, and has a particle size of <0.16 mm.
3. The graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The sheet diameter of the graphene oxide is 0.5-3 μm, and the thickness is 1.1-1.2 nm.
4. The graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The particle size of the slag is less than 40µm, and the sum of its CaO, MgO, SiO2 and MnO contents is greater than 90%; the SiO2 content of the metakaolin is 40-60%, the Al2O3 content is 30-50%, and the loss on ignition is ≤5%; the particle size of the limestone powder is less than 1mm, and its CaO content is 40-60%, the SiO2 content is 20-40%, the Al2O3 content is ≤10%, and the loss on ignition is ≤5%.
5. The graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 1, characterized in that: The particle size of the quartz sand is 10-70 mesh, its SiO2 content is 90-99%, and its Fe2O3 content is 0.02-0.06%; the particle size of the quartz powder is 300-400 mesh, and its SiO2 content is 90-99%.
6. A method for preparing the graphene oxide reinforced recycled aggregate ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: 1) Mix cement, metakaolin, limestone powder, slag, recycled micropowder, quartz sand and quartz powder, and stir at high speed to obtain a solid mixture A; 2) Pre-wetting the regenerated sand to obtain regenerated sand in a saturated surface dry state; Adding the regenerated sand in a saturated surface dry state into the solid mixture A and stirring at high speed to obtain a solid mixture B; 3) Mix polycarboxylate water reducer, graphene oxide and water, the amount of water used is the total water consumption minus the water absorption of the regenerated sand in the saturated surface dry state, stir evenly to prepare dispersion C; 4) The solid mixture B is placed in a high-speed stirring state, and the dispersion C is sprayed therein for 30 to 60 seconds every 1 to 2 minutes until the two are completely mixed. The total time is controlled within 10 to 15 minutes to obtain a solid-liquid mixture D; 5) Add steel fiber to the solid-liquid mixture D and stir at high speed to obtain a mixture E; 6) The mixture E is placed into a mold and covered with a film. After hardening and forming, the mold is removed and cured to obtain graphene oxide reinforced recycled aggregate ultra-high performance concrete.
7. The method for preparing graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 6, characterized in that: The high-speed stirring rate is 2000-3000 rpm, and the stirring time in step 1), step 2), and step 5) is 5-8 min.
8. The method for preparing graphene oxide reinforced recycled aggregate ultra-high performance concrete according to claim 6, characterized in that: The curing temperature is 20±2°C, the humidity is >95%, and the curing time is 7 to 28 days.
Citation Information
Patent Citations
Cement board and semidry method preparation technology thereof
CN109608134A
Graphene oxide ultra-high performance concrete with low cement consumption and preparation method thereof
CN111377687A
Environment-friendly quartz mine tailing mud white ultra-high performance concrete material and preparation method thereof
CN113121168A
Ultra-high performance concrete based on internal curing of recycled fine aggregate and preparation method of ultra-high performance concrete
CN113816696A